Powder metallurgical materials and products. Methods of testing and chemical analysis of hardmetals. Chemical analysis by flameatomic absorption spectrometry. Determination of calcium, potassium, magnesium and sodium in contents from 0.001 to 0.02% (7Im/m7R) Part 4.17.2, (30th June 1986) - British Standards Institution,
No abstract available